TAHLÎL AL-AKHTHÂ AL-SYAFAHIYAH AL-SYÂI’AH LADA THULLÂB QISM TA’LÎM AL-LUGHAH AL-‘ARABIYAH FÎ AL-JÂMI’AH AL-ISLÂMIYAH AL-HUKÛMIYAH BI MALANG - Bahruddin, Uril; Halomoan, Halomoan (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2019)
This study aims to describe the oral errors of Arabic department students which include types, classification, percentage and cause of errors. This study used a qualitative approach with descriptive type. Data is taken from 16 of arabic department’s students in thirdsemester. The results of this study (1) There are three types of verbal errors, namely: phonological, vocabulary and structure, (2) Phonology errors include misreading of diacritical mark and sounds that have similarities and replacing verbs diacritical mark. Vocabulary errors include improper use and use of the Indonesian language. Structural errors include i'rob, alif and lam in the mudlof and the use of Indonesian language structures, (3) Percentage of errors includes 8% in phonolgical, 17% in vocabulary, and 74% in structure, (4) The cause of error is due to: the influence of the mother tongue, the environment that does not support, the teacher who does not set an example and the interference in Arabic.